LAYANAN BIMBINGAN DAN KONSELING DI MASA NEW NORMAL - Ahmad Almafahir (Penerbit Lafadz Jaya, 2021)
The government has issued regulations regarding efforts to prevent the spread of the Covid-19 pandemic in Indonesia. One of them is by imposing new normal behaviour or new normal. The education sector is one of the areas affected, including guidance and counseling services. This study aims to determine the effective services in counseling guidance in the new normal period. This research uses the type of library research or library research. The technique for collecting data is through the study of various reference sources related to the article's theme. The study results show that several madrasah counseling guidance services can be applied in the new normal period, including home visit services, direct meeting programs, cyber counseling and counseling cinema.